Three‐dimensional modeling of high‐latitude scintillation observations. Issue 7 (15th July 2016) - Chartier, Alex; Forte, Biagio; Deshpande, Kshitija; Bust, Gary; Mitchell, Cathryn
Abstract: Global Navigation Satellite System signals exhibit rapid fluctuations at high and low latitudes as a consequence of propagation through drifting ionospheric irregularities. We focus on the high‐latitude scintillation problem, taking advantage of a conjunction of European Incoherent Scatter Radar (EISCAT) observations and a GPS scintillation monitor viewing the same line of sight. Just after 20:00 UT on 17 October 2013, an auroral E region ionization enhancement occurred with associated phase scintillations. This investigation uses the scintillation observations to estimate the ionospheric electron density distribution beyond the spatial resolution of EISCAT (5–15 km along the line of sight in this case). Following the approach of Deshpande et al. (2014), signal propagation is modeled through a specified density distribution. A multiple phase screen propagation algorithm is applied to irregularities conforming to the description of Costa and Kelley (1977) and constrained to match the macroscopic conditions observed by EISCAT. A 50‐member ensemble of modeled outputs is approximately consistent with the observations according to the standard deviation of the phase ( σp ). The observations have σp = 0.23 rad, while the ensemble of modeled realizations has σp = 0.23 + 0.04–0.04. By comparison of the model output with the scintillation observations, we show that the density fluctuations cannot be a constant fraction of the mean density. The model indicates that E region density fluctuations whose standard deviation varies temporally between 5 and 25% of the mean (EISCAT‐observed) density are required to explain the observed phase scintillations. Key Points: High‐latitude E region irregularities modeled with 3‐D multiple phase screens Model ingests EISCAT electron density observations Model results provide a reasonable match to GPS observations